Experimental and computational studies of the hydrodynamics of the riser of a circulating fluidized bed - Farid Nasir Ani, 1957-; International Conference on Engineering and Technology (2005 : Brunei) (Skudai : Universiti Teknologi Malaysia, 2005)
50